KEANEKARAGAMAN JENIS BURUNG PADA BEBERAPA PROFIL HABITAT DI HUTAN LINDUNG GUNUNG MAHAWU, MASARANG DAN TAMPUSU - Asran A. Tharo; Hard N. Pollo; Johny S. Tasirin (COCOS, 2022)
ABSTRACT Birds that are not able to adapt to changes in land from forest to non-forest will look for a place of removal to become a new area of life. The use of space in the forest profile, both vertically and horizontally in various habitat types, shows a close relationship between birds and their habitat, especially in terms of adaptation patterns. The vertical distribution of bird species can be seen from the spatial stratification of the forest profil.The purpose of this study was to determine the diversity of bird species in several habitat profiles in the Protected Forest of Mount Mahawu, Masarang dan Tampusu. The Methods used in this study were the IPA-Count Method ( Index point of abudance) and the rapid assessment method. The results showed that there were 3 habitat profiles in the Mount Mahawu Protected Forest as many as 31 bird species with the Shannon-wiener Diversity Index of 2.27. There are 3 habitat profiles in the Mount Masarang Protection Forest as many as 34 bird species with the Shannon-wiener Diversity index of 2.15. There are 3 habitat profiles in the Mount Tampusu Protection Forest as many as 27 bird species with a Shannon wiener Diversity index of 2.31. The total habitat profile is 4 profiles, 43 species, 34 genera, 23 families with the shannon-wiener Diversity index of 6.73. Keywords : Birds, Diversity of bird species, Protected Forest of Mt. Mahawu, Masarang and Tampusu